Hospitalized Young Adults' Expectations of Pastoral Interventions. (March 2013) - Piderman, Katherine M.; Jenkins, Sarah M.; Hsu, Jennifer S.; Kindred, Alexander S.
The objective of this analysis of 4500 inpatients was to identify the experience and expectations of 18–35 year olds regarding chaplain visitation and to compare results with data from older adults. 71% of young adults reported wanting to be visited by a chaplain; 45.5% were visited; 68% indicated that this was important. Young adults value chaplains' role as a sign of God's care and presence (77.4%), in providing support for family (73.6%), being present during times of anxiety (66.0%), and praying/reading scripture with them (62.3%). Results were similar to older respondents, but young adults were more likely to value ethical counsel from chaplains (58.5% vs. 38.2%). This study provides clinically relevant information and suggestions for further research.